Dynamics modeling and sliding mode control of tractor-trailer wheeled mobile robots subject to wheels slip - Alipour, Khalil; Robat, Arsalan Babaei; Tarvirdizadeh, Bahram (Mechanism and machine theory, 2019)
•A dual-platform wheeled mobile robot has been considered.•The considered wheeled robotic system is modeled while the lateral and longitudinal slippages of wheels are taken into account.•A novel robust sliding mode controller is proposed to trajectory tracking of the considered robotic system. Wheeled mobile robots have vast applications in various areas of technology, and hence improving their autonomy has been the subject of extensive research. To enhance the payload carrying capacity of single-platform wheeled robots, an additional wheeled platform (called trailer) is connected to the active platform (called tractor) and the whole system is called the Tractor-Trailer Wheeled Mobile Robot (TTWMR). In the present study, a novel control rule is presented for trajectory tracking control of such robotic systems. To this end, the dynamics model of such nonholonomic systems is for the first time derived such that lateral and longitudinal slip in the wheels are taken into account. To model the interaction between the wheels and the ground, the LuGre friction model has been utilized. Then, the obtained dynamics model has been verified using ADAMS multibody simulation software. In the next step, to track the desired trajectories, a novel controller, based on sliding mode robust approach, is suggested in which slipping is modeled as a set of unknown but finite disturbances in the robot model. Validity and accuracy of the proposed controller have been examined via computer simulations.